Smart Cities and Socio-Economic Development in Nigeria: Evidences from some selected Countries. - Okewale, Raheem Akanni; ATOBATELE, ABOLAJI JAMIU (Annals of Spiru Haret University. Economic Series, 2022)
The rate at which cities are growing over decades with unprecedented increase in the use of utilities such as water, energy, education, housing, sanitation etc. calls for concern. The unprecedented population growth has led to the agitation for smart cities where little efforts will be utilized to achieve maximum output. However the government of Nigeria has put in place some measures to achieving smart city concept that will assist the citizens to live better life that will lead to a robust socio-economic, despite this feat the country has not explored the concept maximally to increase better living that will engender a robust socio-economic development. Sequel to this background that this study examines the role plays by smart cities in ensuring socio-economic development in Nigeria. The secondary data used in this study was gathered from existing publications. Being a qualitative research, content analysis was employed in the interpretation of the data. It was revealed that smart city arrangement in Nigeria is poor, hence this affect socio-economic activities most especially in the areas of trade and commerce, education, security, health to mention but a few. The study therefore recommends that government should encourage private sector through public private partnership to achieve this feat.